Socio-economic Development of Regions of Russia: Assessment of the State and Directions of Improvement - Slepneva, Ljudmila Romanovna; Tsyrenov, Dashi Dashanimaevich; Kokorina, Anna Andreevna; Slepneva, Julija Valer’evna; Munkueva, Irina Sergeevna (International Journal of Economics and Financial Issues, 2016)
The article is devoted to the development of an effective method of assessing the level of socio-economic development of regions. On the basis of generalization of existing approaches (expert assessments and rating, calculation of individual analyical and complex (generalizing) values, determination of the system of quantitative and qualitative characteristics, the calculation of integrated indicators and indices), there is suggested the authors’ method of estimating the level of socio-economic development of regions. The main distinction of the refined authors’ methodology is the use of a limited number of indicators (five indicators of the economic development and five indicators of the social development), objectively characterizing the state and dynamics of the economic and social processes taking place in the regions. The result of the calculation with the use of the revised methodology is the indicative assessment of the level of economic and social development, on which a matrix is constructed that allows to determine the type of the region and acceptable strategic directions for the foreseeable future. In the paper, comparative characteristic of the socio-economic development of regions of Russia on an example of the Siberian Federal District is presented, there are identified regions - regions-leaders and "problematic" regions. Typology matrix of the regions of the Siberian Federal District in terms of social and economic development is elaborated. It is shown that for each group of regions, similar directions of socio-economic development can be applied. Keywords: differentiation of regions, regional asymmetry, social and economic development, JEL Classifications: R11, O18